Sujeitos e projetos em disputa na origem dos conselhos de políticas públicas - Ribeiro, Natalina (2011)
The thesis examines the historical origins of the debate on policy councils through the trajectory of subjects, projects and proposals in dispute in Brazilian society. The survey is based on the analysis of documents and literature, complemented by interviews with privileged persons of the studied dynamics. In the process of the survey, the area of health policies was focused on for its pioneer role in the implementation of channels for popular participation, created as a result of the dynamics and struggles brought about by the popular movements for health care and sanitarian, foremost protagonists of the initiatives that originated the health councils, acknowledged as a reference for other public policies. Supported by its consolidated legitimacy together with the people represented, these actors craved for the construction of spaces of dispute within the State and the conquest of the right to interfere in the health policies. As such, in the context of the military dictatorship (1964-1984) and under the influence of international agencies, we observe the inclusion of these sectors of the opposition in various instances of the state apparatus, designed as a strategy for the struggle for rights, the appropriation and resignification of the concepts and spaces hegemonized by the authoritarian project. As a result of these struggles, the councils were implemented in the early 1990s, at the same time as neo-liberal adjustment measures were imposed by the International Monetary Fund (IMF). In this adverse situation, the councils constituted themselves as mechanisms of resistance, social control and propositions, with the potential to articulate actors and proposals within the perspective of democratic construction. The survey concludes that such a potential can only be realized insofar as they are inserted in the strategies of a democratic political project, capable of providing backup to the counselors in their struggles, giving a collective meaning to the exercise of participation. At the moment, it remains to be seen what space and role the councils have in the construction of the dispute for hegemony in Brazil